2021
DOI: 10.1016/j.psj.2021.101245
|View full text |Cite
|
Sign up to set email alerts
|

Prospects for the utilization of Senna obtusifolia products as protein supplements for poultry

Abstract: The scarcity and high cost of conventional ingredients are major factors limiting the growth of the poultry industry globally. This has driven research into alternative ingredients for poultry feeding. Senna obtusifolia or cassia, a widely distributed shrub, is invasive in many regions of the world. The seeds and leaves of the plant are moderate protein sources with the protein having an acceptable amino acid profile, especially essential amino acids. This nutritional profile of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 40 publications
1
5
0
Order By: Relevance
“…This present study showed that fermentation and inclusion levels both affected the weight gained. This agrees with the findings of some studies [40][41][42][43][44] , that one of the major limitations of using alternative plant protein sources in fish feeding is the changes in palatability and the presence of anti-nutrition factors in the ingredient. The reduction in feed intake due to the unpalatability may lead to deterioration in growth performance and feed utilization.…”
Section: Discussionsupporting
confidence: 92%
“…This present study showed that fermentation and inclusion levels both affected the weight gained. This agrees with the findings of some studies [40][41][42][43][44] , that one of the major limitations of using alternative plant protein sources in fish feeding is the changes in palatability and the presence of anti-nutrition factors in the ingredient. The reduction in feed intake due to the unpalatability may lead to deterioration in growth performance and feed utilization.…”
Section: Discussionsupporting
confidence: 92%
“…What is more, oxalate and phytate also show negative impact on protein and lipid utilization [35]. Values of 5 g•kg −1 and 20 g•kg −1 oxalate in diet cause toxicity to monogastric and ruminant animals, respectively [36]. The content of phytic acid, an anti-nutritional factor in fava beans, ranges from 19.65 g•kg −1 DM to 22.85 g•kg −1 DM.…”
Section: Discussionmentioning
confidence: 99%
“…But in this study, the content of oxalic acid and phytic acid in PM was 0.89 g•kg −1 and 1.27 g•kg −1 DM, respectively, indicating that oxalate and phytate in PM showed no negative impact. Researchers have reported that diets with more than 5 g total tannin/kg would reduce fodder intake in chickens and increase mortality in rats [36]. In addition, young animals were more sensitive to dietary TT than adult animals.…”
Section: Discussionmentioning
confidence: 99%
“…The growth of the poultry industry globally can be limited by the scarcity and high cost of conventional feedstuffs ( Diarra, 2021 ), leading us to find alternative feedstuffs for poultry. Soybean meal ( SBM ) was widely used in poultry diets due to the good nutritional value with high digestibility of crude protein ( CP ) and amino acids ( AA ).…”
Section: Introductionmentioning
confidence: 99%